Rape Trials in England and Wales Observing Justice and Rethinking Rape Myths - Smith, Olivia (Springer International Publishing, 2018)
In light of ongoing concerns about the treatment of survivors, Rape Trials in England and Wales critically examines court responses to rape and sexual assault. Using new data from an in-depth observational study of rape trials, this book asks why attempts to improve survivor experiences at court have not been fully effective. In doing so, Smith identifies deep-rooted barriers to survivor justice and, crucially, introduces potential avenues for more effective reform. This book provides a comprehensive examination of the practicalities of court, use of rape myths and sexual history evidence, underlying principles of adversarial justice and the impact of inequalities embedded within English and Welsh legal culture. This engaging and highly significant study is essential reading for anyone seeking to understand the criminal courts and their responses to rape, including practitioners and students of criminology, sociology, and law. .